2015
DOI: 10.1370/afm.1820
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Sexual Activity and Satisfaction in Midlife and Older Women

Abstract: PURPOSE Sexual activity is an important component of quality of life for women across their lifespan. Prior studies show a decline in sexual activity with age, but these studies often fail to consider the role of sexual satisfaction. The aim of this study is to give updated prevalence estimates of sexual activity among women and to elucidate factors associated with sexual activity and sexual satisfaction. METHODSWe report a cross-sectional analysis of the second wave of a nationally representative sample of US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
1
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 27 publications
9
57
1
13
Order By: Relevance
“…In that study, the prevalence of sexual activity was 40.5% among 3,145 participants who reported using antihypertensive medications. The results of our study and others confirm that sexual activity is prevalent among many older women with HTN 31 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In that study, the prevalence of sexual activity was 40.5% among 3,145 participants who reported using antihypertensive medications. The results of our study and others confirm that sexual activity is prevalent among many older women with HTN 31 .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we did not ask why participants had not engaged in sexual activity, and thus we cannot determine whether sexually inactive participants also had sexual dysfunction. Also, although SPRINT assesses living arrangement, we did not initially ask participants regarding relationship status, availability of a sexual partner 31 ; or the health or sexual function of partners, each of which may influence sexual activity and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the predictors of increased satisfaction in SWAN were psychosocial as opposed to physical; availability of a partner (especially a new partner), higher ratings of the importance of sex, fewer mood symptoms, and more positive attitudes about aging were associated with better emotional and physical sexual satisfaction. A cross-sectional analysis of 1345 women in the second Midlife in the United States (MIDUS 2) study likewise found that menopause status was not associated with overall sexual satisfaction, but psychosocial variables, including relationship satisfaction, communication with one’s partner, and importance of sex were associated with overall sexual satisfaction (36). These findings suggest that while some aspects of physical sexual function may decline during midlife, sexual satisfaction appears to be stable.…”
Section: Changes In Sexual Function Over the Menopause Transitionmentioning
confidence: 99%
“…Studies of sexuality and aging in older adults who enjoyed the benefits of sexuality throughout their lives (Laumann et al, 2006;Thomas, Hess, & Thurston, 2015) supported the idea that continuing active sex lives into later life contributed to quality of life and increased life satisfaction. From a classic study (Bergström-Walan & Nielsen, 1990) to a recent examination of aging Iranian women (Ravanipour, Gharibi, & Gharibi, 2013), it is apparent that sexual interest in older adults remains a vital part of relationships.…”
Section: Positive Factorsmentioning
confidence: 98%